Spreading and Controlling of HIV-AIDS in Semarang City 2013-2021 - Novita Sapitri, Siti; Utama, Nanda Julian (Universitas Negeri Semarang, 2024)
This article describes the spread of and response to HIV in Semarang City, particularly from 2013, when Semarang City Regional Regulation No. 4/2013 was issued, until 2021, when the Komisi Penanggulangan AIDS (KPA) Semarang City was merged into the Dinas Kesehatan Kota (DKK) Semarang. The average number of HIV cases that occurred in Semarang City during 2013-2021 was 535. This paper aims to examine how the conditions of Semarang City affect the spread of HIV, as well as how the HIV-AIDS response was carried out by the Semarang City government from the beginning of the issuance of Semarang City Regional Regulation Number 4 of 2013 until the dissolution of Semarang City KPA in 2021. The method used in this research is the historical research method, in the form of: collecting sources (heuristics); verifying the sources found (source criticism); interpreting the sources (interpretation); and presenting in written form (historiography). During the writing process, the author collected various types of sources ranging from interviews, archives, books, and journal articles obtained from various related institutions through both offline and online processes. The author also conducted direct research in the field. The results of this paper map the distribution of PLWHA by health center, explain the development of VCT services in Semarang City, HIV cases from 2013-2021, and government efforts in tackling HIV/AIDS in Semarang City. Semarang City, which often holds the first position of the largest number of HIV cases throughout Central Java, continues to maximize the HIV prevention process. The increasing number of cases is considered the success of the government and its staff in reaching PLHIV through VCT programs that are routinely carried out in health facilities. Programs conducted by the city government in collaboration with agencies included in the KPA membership can be said to be increasingly efficient every year. Various prevention activities that directly approach Key Populations (Populasi Kunci/Ponci) have been carried out until now